1977
DOI: 10.1083/jcb.74.2.531
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of phospholipid vesicles to Chinese hamster fibroblasts: Role of cell surface proteins

Abstract: The adhesion of artificially generated lipid membrane vesicles to Chinese hamster V79 fibroblasts in suspension was used as a model system for studying membrane interactions. Below their gel-liquid crystalline phase transition temperature, vesicles comprised of dipalmitoyl lecithin (DPL) or dimyristoyl lecithin (DML) adsorbed to the surfaces of EDTA-dissociated cells. These adherent vesicles could not be removed by repeated washings of the treated cells but could be released into the medium by treatment with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0
1

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(37 citation statements)
references
References 37 publications
0
36
0
1
Order By: Relevance
“…Pires et al (1999) demonstrated that liposomes made up of PC:PE displayed low cell-binding ability and extremely limited cell fusion, which suggested that neutral liposomes are internalized mainly by an endocytic mechanism. Although the exact endocytosis mechanism responsible for the uptake of neutral liposomes is still unclear, it has been speculated that such a mechanism may involve the binding of liposomes to a trypsin-sensitive site (Pagano and Takeichi, 1977). In fact, it was demonstrated that the interaction of neutral PC liposomes to Chinese hamster V79 fibroblasts could only be dissociated in the presence of trypsin (Pagano and Takeichi, 1977).…”
Section: A Conventional Liposomes-negatively Charged and Neutral Lipmentioning
confidence: 99%
See 1 more Smart Citation
“…Pires et al (1999) demonstrated that liposomes made up of PC:PE displayed low cell-binding ability and extremely limited cell fusion, which suggested that neutral liposomes are internalized mainly by an endocytic mechanism. Although the exact endocytosis mechanism responsible for the uptake of neutral liposomes is still unclear, it has been speculated that such a mechanism may involve the binding of liposomes to a trypsin-sensitive site (Pagano and Takeichi, 1977). In fact, it was demonstrated that the interaction of neutral PC liposomes to Chinese hamster V79 fibroblasts could only be dissociated in the presence of trypsin (Pagano and Takeichi, 1977).…”
Section: A Conventional Liposomes-negatively Charged and Neutral Lipmentioning
confidence: 99%
“…Although the exact endocytosis mechanism responsible for the uptake of neutral liposomes is still unclear, it has been speculated that such a mechanism may involve the binding of liposomes to a trypsin-sensitive site (Pagano and Takeichi, 1977). In fact, it was demonstrated that the interaction of neutral PC liposomes to Chinese hamster V79 fibroblasts could only be dissociated in the presence of trypsin (Pagano and Takeichi, 1977).…”
Section: A Conventional Liposomes-negatively Charged and Neutral Lipmentioning
confidence: 99%
“…The sharp decrease in the DPPC amount bound to the surface at the gel-liquid crystal transition (P~,-L~ fluidization, Fig. 4) correlates with some findings concerning cell adhesion: various types of cells adhere to solid lipid films but not to fluid films [20][21][22]; solid liposomes more strongly associated with cells than fluid liposomes [23,24]; fluidization of cell membranes reduces cell adhesiveness [7][8][9][10][11][12][13]. This, as well as the electron microscope investigation (Fig.…”
Section: Discussionmentioning
confidence: 59%
“…Adsorbed vesicles can be released by treatment with trypsin, but not by repeated washing [2,12]. In our case, trypsin failed to reduce the proportion of phosphatidylcholine bound to protoplasts (table 1).…”
Section: Discussionmentioning
confidence: 79%